Opini Pemilih Pemula Surabaya terhadap Iklan Politik Para Kandidat di Pilkada - Agusly Irawan Aritonang (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
Election Campaign Period is a period in political events where candidates have the opportunity to introduce themselves to the public. Through various forms and channels of communication, candidates endeavor to convey their ideas and profile. One form of communication channel is political advertising. The target group that is always interesting to be targeted by advertisements is the beginner voter group. With a very significant number of them, the beginner voter is a potential "market" to work on so that a candidate's campaign message can be conveyed. This study wants to see how the opinions of the beginner voters, especially in the city of Surabaya about the ads of candidates for Cagub Cawagub in the East Java Regional Election 2018. Using a quantitative approach with survey methods, the results show that both candidate pairs' ads, namely Khofifah-Emil and Gus Ipul- Puti are positively opinion by beginner voters. However, when viewed from each opinion component, namely Trust, Values, and Expectations, the Gus Ipul-Puti advertisement has a higher component in Values and Expectations while the Khofifah advertisement pair is high in the Trust component.